Effect of motivational interviewing on treatment adherence and self‐efficacy of adolescents with asthma: A randomized controlled trial - Fatemeh Taheri; Ahmad Nasiri; Somayeh Namdari; Fatemeh Salmani (Wiley, 2023)
Abstract Aims This study examined the short‐term effect of motivational interviewing on treatment adherence and self‐efficacy of adolescents with asthma. Design The randomized controlled trial. Method In this study, 72 adolescents with asthma were recruited and assigned to experimental and control groups randomly. In the experimental group, the motivational interviewing was performed for five weekly sessions lasting 80-90 min. The treatment adherence and self‐efficacy questionnaires were completed before the intervention, 2 weeks and 3 months after the intervention in both groups. Data were analysed by Chi‐Square test, independent samples T‐test, repeated measures of Wilcoxon and generalized estimating equation. Results The treatment adherence was found to be significantly higher 2 weeks (p = 0.006) and 3 months after the intervention (p = 0.04) in the experimental group than the control group. In addition, the degree of self‐efficacy was significantly more in the experimental group 2 weeks (p < 0.001) and 3 months later (p < 0.001) than the control group. The result of generalized estimating equation showed that the intervention group had an average of 14.44 more self‐efficacy points than the control group (p < 0.001). Also, treatment adherence in the intervention group was significantly higher than the control group (β = 6.14, p = 0.05(. Conclusion This study adds to the evidence for the effectiveness of motivational interviewing in treatment of adolescents with asthma.